John Summerfield correspondence - Summerfield, John, 1798-1825.
Letter (Burlington) from Summerfield to his sister, Ellen Summerfield Blackstock, discussing family matters.
Clergyman of the Methodist Episcopal Church.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Blackstock, Ellen Summerfield -- Correspondence; Methodist Episcopal Church -- Clergy -- Correspondence; Clergy